X- RAY POWDER DIFFRACTION DATA FOR SODIUM MORPHOLYLDITHIOCARBAMATE TRIHYDRATE C5 H8 NOS2 NA 31120 - Rodríguez, Joelis (Universidad de Panamá. Facultad de Ciencias Naturales, Exactas y Tecnología, 2002)
Sodium Morpholyldithiocarbamate Trihydrate C5H8NOS7Na 3H,0 has beeninvestiated by means of X-ray powder diffraction. The title compound is triclinicwith unit-cell parameters a= 6.261 (2) b = 8.897 (3) c = 16.557 (4) A: a 118.34(2) í3 = 99.66 (2) y = 93.32 (3) °, V = 790.2 (3)A3, Z =2 . space group P 1 andDx= 1.007(12)gcm 3.